The song of songs and the fashioning of identity in early Latin christianity - Shuve, Karl (Oxford Oxford University Press, 2016)
Karl Shuve offers a comprehensive analysis of the interpretation of the 'Song of Songs' in the Latin-speaking churches of late antiquity, showing how it was used by bishops and theologians to illuminate complex problems of identity in relation to liturgical practice, doctrinal definitions, and ideas about the body and sexuality
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc -- Europe -- History; Identity (Psychology) -- Religious aspects -- Christianity; Theology, Doctrinal -- History -- Early church, ca. 30-600; Bible ; Song of songs ; Criticism, interpretation, etc ; Europe ; History; Theology, Doctrinal ; History ; Early church, ca. 30-600; Identity (Psychology) ; Religious aspects ; Christianity